Aplikasi bambu pada struktur gableframe =Bamboo Apllication on Gable Frame Structure - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
Bamboo is a cheap building material which can be found easily. It has been used as building material in Indonesia since a long time ago. The problem of joining bamboos limits the applications only for a Simple and light structure. Method of joining bars was treated in traditional ways, using nails made of timber and rope. The strength of the joint depends on the skill of workers, usually it is very low, and depend on many other factors that make it difficult to analyse. Research on tensile and shear joints of bamboo were conducted experimentally using 2 bolts of 12 mm in diameter. Hydraulic jack was installed on loading frame to generate loading. The diameter and thickness of bamboo were chosen to be the free variables while spacing and diameter of bolt as well as quality of material were the fixed variables. The results were analysed and compared to existing formula. The type of joint was applied to a gable frame structure of 10.80 m span, and 6.5 m height. The results showed that the comparison between experimental and theoretical, for tension was 105.444 % in average with standard deviation of 18.689 %, whereas for shear joint were 91.474 % and 14.291 %. From the test it was found that the strength of tension joint vary between 26 KN to 48.16 KN and 37 KN to 76.5 KN for shear joint. The test for 3 models of structure showed that actual deflections were bigger than allowable deflection. From analysis using SAP90 for various proposed models it was found that decreasing the span is unable to reduce the deflection. It means that bamboo is not suitable for frame structure, but suitable only for truss structure.